REINCARNATION OR HALLUCINATION? THE REVIVAL (OR NOT) OF THE AMENDE HONORABLE - André Mukheibir (Obiter, 2022)
For once it seems almost appropriate to say “in with the old”. The last ten years have seen many new developments being introduced into the law, and it has been almost unheard of to unearth relics from the past. Yet this is precisely what has happened over the last two years with a remedy that had been all but forgotten, the so-called amende honorable. It was generally accepted that this remedy had fallen into disuse, when, lo and behold, it suddenly made an appearance in 2002 in the Witwatersrand Local Division. In 2003 it appeared again in the South, albeit much more tentatively. The possible recurrence of this old remedy is very telling in this modern, constitutional era, where it has become more appropriate most of the time to discard the old. But let us start at the very beginning ...